Design and Implementation of a Functional Electrical Stimulator - Abu Snan, Mohammad; Hamarsheh, Noor (جامعة بوليتكنك فلسطين - اتمتة صناعية, 2009)
In this project thanks to God, there had been accomplished a design and a study of an Electrical Stimulation Device, which is used to compensate for Nerves Signal when it suffers from a partial or complete paralysis, so as to get the electrical activity of muscles to prevent shrinking using special electrodes that is fastened on the patient skin. The project gives the capability of adjustment of frequency, current amount, electrical voltage and the type of electrical stimulation in a way to fit the sensitivity, place and degree of paralysis that the patient suffers from, and it is usually used in the cases of Physiotherapy in clinics and hospitals. This documentation includes the detailed design of the project and the stages which were followed in order to reach to the desired goals of the project, those are represented as designing and studying each partial stage of whole project’s stages each one aside, then to collect or assemble these stages as a one integrated unit. ملخص المشروع في هذا المشروع تم بحمد الله دراسة وتصميم جهاز التحفيز الكهربائي ,الذي يستخدم للتعويض عن اشارة الأعصاب (السيال العصبي), عندما يحدث لها شلل كلي اوجزئي , لكي نحصل على النشاط الكهربائي للعضلات لمنع ضمورها باستخدام الكترودات خاصة تثبت على سطح جلد المريض. المشروع يمكننا من ضبط التردد وكمية التيار والجهد الكهربائي ونوع التحفيز الكهربائي, بما يناسب حساسية و مكان ودرجة الشلل عند المريض, و يستخدم في العلاج الطبيعي في العيادات والمستشفيات. يحتوي هذا التقرير على التصميم التفصيلي للمشروع والمراحل التي تم اتباعها من أجل الوصول إلى الأهداف المرجوة من هذا المشروع والتي تتمثل في تصميم ودراسة كل مرحلة جزئية من مراحل المشروع على حدة، ثم تجميع هذه المراحل كوحدة واحدة.
no of pages 86, 23703, اتمتة صناعية 3/2009 , in the store
Keywords: Electrical Stimulator